The welfare of now and the green (post) politics of the future - Catney, P.; Doyle, Timothy (Sage, 2011)
This paper examines how key differences in the very manner in which the environment/welfare nexus is experienced and understood in both the global North and the global South are managed in favour of the former over the latter. We show how in the case of the global North – the more affluent world, such as Britain – environmental issues have been usually construed as post-materialist and/or post-industrialist. We argue that predominantly Northern-based post-materialists see environmental welfare (largely through the rhetoric of sustainable development and ecological modernization) as either something separate from humans (for the welfare of the ‘rest of nature’) or for the welfare of unborn, future generations. We use the concept of the ‘post-political’ to interpret how the global North dominates debates on the environment and how it can be quite dismissive, and even negligent, of welfare issues in the global South. In the case of the majority world, green welfare policy agendas are littered with the consequences of environmental devastation incurred through centuries of Northern oppression and resource exploitation. In the global South green welfare goals concentrate on the alleviation of those more basic needs of survival – provision of shelter, water availability, air quality, food sovereignty, and energy security – for those humans actually living on the planet; rather than those who may at some time in the future. In short, issues of environmental debt are writ large, rather than those of an imagined environmental future.